A review of N+ observations in the ionosphere-magnetosphere system - Ilie, Raluca; Lin, Mei-Yun; Bashir, Muhammad Fraz; Majumder, Abhiraj (Frontiers in Astronomy and Space Sciences, 2023)
Most studies have yet to consider and assess the transport and energization of N + ions throughout the ionosphere-magnetosphere system, in addition to that of O + and other heavy ion species. The limited observational record of N + presence in near-Earth plasma, partly due to instrument limitations to distinguish ion species of similar masses, has obscured its significant contribution to the near-Earth plasma. This letter reviews the most notable observations of N + ions, starting from the early low altitude measurements from Sputnik III in the ionosphere to the measurements reported by the Enhanced Polar Outflow Probe (e-POP) mission. The available observational data set suggests that nitrogen ions are constant companions of outflowing oxygen ions, and their abundances vary with season, solar cycle, time of day, and geomagnetic activity. This strong record of nitrogen presence in the ionospheremagnetosphere system raises the question of ionic composition and the need for caution when interpreting O + measurements from current missions.